2014
DOI: 10.2147/ott.s65653
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine-induced cardiotoxicity: more evidence or clinical approaches to protect the patients' heart?

Abstract: Fluoropyrimidines, such as capecitabine and 5-fluorouracil, may cause cardiac toxicity. In recent years, the incidence of this side effect has increased and it is expected to further rise due to the population aging and the disproportionate incidence of breast and gastrointestinal cancers in older individuals. The spectrum of cardiac manifestations includes different signs and symptoms and the diagnosis may be difficult. Here, we report the case of a 43-year-old woman with advanced breast cancer who was rechal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…These biomarkers are not highly sensitive to FP-related cardiovascular toxicity. Nevertheless, as cardiovascular toxicity develops, levels of these biomarkers increase abnormally [9,52,55]. In asymptomatic patients, Holter-ECG monitoring may be performed upon incidental findings of abnormal biomarker test results and can lead to successful diagnosis of FP-related cardiovascular toxicity.…”
Section: Biomarkersmentioning
confidence: 99%
“…These biomarkers are not highly sensitive to FP-related cardiovascular toxicity. Nevertheless, as cardiovascular toxicity develops, levels of these biomarkers increase abnormally [9,52,55]. In asymptomatic patients, Holter-ECG monitoring may be performed upon incidental findings of abnormal biomarker test results and can lead to successful diagnosis of FP-related cardiovascular toxicity.…”
Section: Biomarkersmentioning
confidence: 99%
“…It has been shown that this compound has a variety of biological proprieties, involving anti-hyperglycaemic, anti-neoplastic, anti-inflammatory, and antioxidant actions ( Ang et al , 2010 ; Polk et al , 2016 ; Xu et al , 2019 ) . Production of inflammatory mediators is inhibited by BBR according to previous studies ( Lou et al , 2011 ; Fontanella et al , 2014 ). In addition, BBR appears to improve the antioxidant defense mechanism within the cell, involving the activity of glutathione peroxidase (GPx), superoxide dismutase (SOD), and catalase (CAT) while decreasing oxidative stress variables such as malondialdehyde (MDA), NO levels, and protein carbonyl content ( Zhou and Zhou, 2011 ).…”
Section: Introductionmentioning
confidence: 70%
“…Once cardiotoxicity has occurred, the safety of a rechallenge with a modified 5-FU- or capecitabine-based regimen is uncertain, and no widely accepted recommendations have been released. [13] Saneeymehri et al rechallenged capecitabine with a patient who experienced chest pain with 5-FU administration. The cardiac symptoms subsided after initiation of capecitabine and the patient tolerated the treatment well.…”
Section: Discussionmentioning
confidence: 99%